2022
DOI: 10.1177/23259671221125218
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Thresholds of Segmental Femoral Torsion in Patients With Patellar Dislocation: Influence on Patellofemoral Malalignment

Abstract: Background Femoral torsion can be evaluated from different femoral segments. The pathological thresholds for femoral torsion of different segments and the influence of segmental femoral torsion on patellofemoral alignment remain unknown. Purpose To compare femoral torsion between patients with recurrent patellar dislocation and healthy individuals, to determine the statistical physiological range and pathological thresholds of femoral torsion in different segments, and to investigate the influence of femoral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…However, our follow‐up results show that derotational femoral osteotomy still demonstrates good postoperative results for patients in the distal torsion group. Xu et al reported that excessive shaft, distal and total torsion of the femur were associated with more significant patellar tilt [23]. On the one hand, there was a significant increase in supracondylar torsion in this group of patients compared with patients with normal FA, and derotational femoral osteotomy reduced the risk of redislocation by decreasing the lateral sagittal tension in the patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, our follow‐up results show that derotational femoral osteotomy still demonstrates good postoperative results for patients in the distal torsion group. Xu et al reported that excessive shaft, distal and total torsion of the femur were associated with more significant patellar tilt [23]. On the one hand, there was a significant increase in supracondylar torsion in this group of patients compared with patients with normal FA, and derotational femoral osteotomy reduced the risk of redislocation by decreasing the lateral sagittal tension in the patients.…”
Section: Discussionmentioning
confidence: 94%
“…Seitlinger et al and Xu et al reported that high femoral torsion consists of pronation of the femoral neck, external rotation of the femoral shaft and internal rotation of the distal end of the femur [9, 23]. Qiao et al also found that in patients with patellar dislocations, the site of increased FA of the femur is located predominantly at the shaft and distal end of the femur [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high rate of recurrence, tissue damage, and poor functional outcome, patellar dislocation for the first time causes significant morbidity and might represent a reason for sport retirement [6, 19, 27]. The recurrence rate following conservative management is approximately 25%; therefore, receiving proper treatment after the first episode of patellar dislocation has a considerable impact on the outcome [7, 20, 22, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Second, in conservatively treated patients, most surgeons recommended weight-bearing to tolerance and a knee brace during the irst four weeks, with a range of motion of 30° during the irst 15 days and up to 60° for an additional 15 days (Fig. Third, surgical Given the high rate of recurrence, tissue damage, and poor functional outcome, patellar dislocation for the irst time causes signiicant morbidity and might represent a reason for sport retirement [6,19,27]. The recurrence rate following conservative management is approximately 25%; therefore, receiving proper treatment after the irst episode of patellar dislocation has a considerable impact on the outcome [7,20,22,24].…”
Section: Discussionmentioning
confidence: 99%